Mechanical properties of QFP micro-joints soldered with lead-free solders using diode laser soldering technology - 韩宗杰 薛松柏 王俭辛 张昕 张亮 禹胜林 王慧 (Transactions of Nonferrous Metals Society of China, 2008)
Soldering experiments of quad flat package（QFP） devices were carried out by means of diode laser soldering system with Sn-Ag-Cu and Sn-Cu-Ni lead-free solders, and competitive experiments were also carried out not only with Sn-Pb eutectic solders but also with infrared reflow soldering method. The results indicate that under the conditions of laser continuous scanning mode as well as the fixed laser soldering time, an optimal power exists, while the optimal mechanical properties of QFP micro-joints are gained. Mechanical properties of QFP micro-joints soldered with laser soldering system are better than those of QFP micro-joints soldered with IR reflow soldering method. Fracture morphologies of QFP micro-joints soldered with laser soldering system exhibit the characteristic of tough fracture, and homogeneous and fine dimples appear under the optimal laser output power.